1993
DOI: 10.1139/t93-058
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for stress and deformation analysis of rockfill dams

Abstract: Stress–strain parameters for modelling the response of rockfill dams to construction and reservoir filling are examined. Parameters from both laboratory tests and back analysis of existing dams are considered. The influence of physical properties of the material, such as mineral composition, grading curves, grain shape, and grain size, is also examined. The results of the study were applied to Foz do Areia dam in Brazil. Finite element analyses were carried out using selected material parameters to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…7 and calculating the number K used in hyperbolic model (Duncan & Chang, 1970). This number was found equals to 464, which agree with the typical values given by many authors for this parameter such as Duncan et al, 1980;Saboya et al, 1993;Liu et al, 2002;Massiera et al, 2006. The ). Figure 4 shows the variation of the total displacement with respect to dam height for the concrete slab, the downstream face and along the dam axis at the end of reservoir filling (water level at 139 m).…”
Section: Moussaisupporting
confidence: 89%
“…7 and calculating the number K used in hyperbolic model (Duncan & Chang, 1970). This number was found equals to 464, which agree with the typical values given by many authors for this parameter such as Duncan et al, 1980;Saboya et al, 1993;Liu et al, 2002;Massiera et al, 2006. The ). Figure 4 shows the variation of the total displacement with respect to dam height for the concrete slab, the downstream face and along the dam axis at the end of reservoir filling (water level at 139 m).…”
Section: Moussaisupporting
confidence: 89%
“…Saboya and Byrne (1993) and Hunter and Fell (2003) showed that smaller size rockfills have higher shear strength and stiffness. Varadarajan et al (2003) concluded that an increase in the size of the rockfill particles results in higher volumetric strain at the same confining pressure.…”
Section: Calibration Of Materials Parametersmentioning
confidence: 99%
“…Since no triaxial test results are available, pertinent works from the literature (Saboya and Byrne, 1993) are referred in selecting the hardening soil model parameters. Table 2 shows the range of parameters used in the preliminary analysis.…”
Section: Generalmentioning
confidence: 99%
“…Among the material models used in the available studies carried out in recent years, Duncan and Chang's (1970) hyperbolic model is probably the most common. The hyperbolic model has been utilized in a number of similar research successfully (Khalid et al, 1990;Saboya and Byrne, 1993;Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%